Jurassic igneous activity in the Exmouth Sub-basin: Insights from new 3D seismic. Issue 1 (1st December 2019) - O'Halloran, G.; Benson, R.; Dempsey, C.
Summary: A late Jurassic pulse of igneous activity occurred within the Exmouth Sub-basin, with several submarine volcanic extrusive centres evident, along with contemporaneous intrusive feeder systems that fed them. The extrusive volcanics have been mapped on 3D seismic datasets and include cone-shaped vents up to 8 km in diameter and >250 m high with flanking lava flows and volcanoclastic facies. Feeder dykes and more stratiform sill systems have also been mapped, and in some cases the former can be directly related to individual volcanic extrusive complexes. Several wells have penetrated lateral equivalents to seismically defined volcanic intervals. These wells intersected thin sequences of distal volcanic facies – invariably interpreted as "crystal tuffs" which is consistent with them being distal fall deposits from a submarine basaltic/intermediate volcanic centre. Timing of the volcanic activity has been relatively well constrained by the ages of onlapping marine sedimentary sequences. A depositional model in which mafic-intermediate volcanic extrusives were erupted into a submarine setting within intermediate water depths ( 100s m) is proposed, and modern-day analogues discussed.